2014
DOI: 10.1097/adm.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Methamphetamine Disrupts the Menstrual Cycles and Hypothalamic-Pituitary-Ovarian Axis

Abstract: The present data demonstrate that long-term use of MA results in the disruption of menstrual cycles and dysfunction of hypothalamic-pituitary-gonadal axis in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In addition, estrogen is known to protect the heart from ischemic injury [3637]. Shen et al [38] recently reported that function of the hypothalamic-pituitary-ovarian axis is disrupted in women who chronically use methamphetamine and that it remains disrupted following several months of abstinence from the drug. Thus, methamphetamine might negate the cardioprotective benefit of being female by disrupting the hypothalamic-pituitary-ovarian axis and suppressing the production of cardioprotective ovarian hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estrogen is known to protect the heart from ischemic injury [3637]. Shen et al [38] recently reported that function of the hypothalamic-pituitary-ovarian axis is disrupted in women who chronically use methamphetamine and that it remains disrupted following several months of abstinence from the drug. Thus, methamphetamine might negate the cardioprotective benefit of being female by disrupting the hypothalamic-pituitary-ovarian axis and suppressing the production of cardioprotective ovarian hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, cardiovascular toxicity due to prenatal METH exposure in adult offspring exhibits significant sex differences but the reason for this discrepancy is unknown. Shen reported that chronically abused METH disrupts the hypothalamic-pituitary-ovarian axis in women Shen et al (2014), indicating that METH exposure during pregnancy may affect estrogen secretion in female offspring and damage its protective effects on the heart. Gender has different effects on the pharmacokinetics of METH in the placenta.…”
Section: Cardiovascular Toxicitymentioning
confidence: 99%
“…It is unclear why fetal exposure to methamphetamine produces sex dependent effects in the hearts of adult offspring. Shen et al (47) reported disruption of the hypothalamicpituitary-ovarian axis in women who chronically used methamphetamine. This suggests that prenatal exposure to methamphetamine may disrupt ovarian function, resulting in a loss of estrogen-dependent cardioprotection.…”
Section: Methamphetaminementioning
confidence: 99%